Incidence OF HPV and EBV in oral cancer and their clinico-pathological correlation– a pilot study of 108 cases - Shahi Vanshika; Agarwal Preeti; Qayoom Sumaira; Kumar Vijay; Tewari Shikha; Raghuvanshi Shivanjali; Singh Uma Shankar; Goel Madhu Mati (Journal of Oral Biology and Craniofacial Research)
Introduction: Out of all non-communicable diseases, cancer is the leading cause of death in the 21st century. Oral cancer ranks in top ten cancers in the world and oncogenic viruses contribute to its development and are a major preventable risk factor for it. Material and methods: In the present study we intend to find the incidence of HPV and EBV by PCR in 108 sporadic oral cancer patients and study the clinico-pathological variables in agreement to their presence or absence. Results: We found that the incidence of EBV in oral cancer is much higher (30/108; 27.8%) than HPV 16 (14/108; 13%) and, a complete absence of HPV 18 (0/108) was reported by real time PCR. Co-infection by EBV and HPV was reported in 5.6% cases (6/108). However, on comparing this data with the corresponding clinico-pathological cofactors (age, gender, grade of tumour, tumour size, nodal status, metastasis, DOI, TIL, ENE) it was found that there was no statistical significance between the two. Conclusion: Hence, we conclude that these oncogenic viruses are independent cofactors to oral cancer development and none of the clinico-morphologic variable is associated with the viral etiology.